The Meaning of Beauty in Rare Beauty Video Advertisement - Ni Wayan Alan Mirani; Komang Dian Puspita Candra; Desak Putu Eka Pratiwi (Journal of Humanities, Social Science, Public Administration and Management (HUSOCPUMENT), 2021)
The researchers are tried to identify the meaning of beauty in Rare Beauty video advertisement. The data of this study were taken from one video on Rare Beauty Instagram account. Observation method was conducted in collecting the data through documentation and note-taking technique. The data were analyzed with descriptive qualitative method. The researchers used theory of meaning proposed by Barthes (1967) to identify the meaning of beauty in Rare Beauty video advertisement. The researchers found three meaning of beauty in Rare Beauty Video Advertisement. The first meaning of beauty is everyone is beautiful with their own uniqueness and there is no such a standard to consider as beauty. The second meaning of beauty is when the women are confident in expressing their beauty they will be happy. The third is everyone is different and the difference has to consider as the uniqueness so the women have to be confident because they are special. The last meaning of beauty is all women are beautiful with their skin tones, shapes and styles. Whatever their skin tones, their styles, they don’t need to compare themselves to the others because they are beauty in their own way.